2009
DOI: 10.2527/jas.2008-0974
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestion and performance by lambs and steers fed thermochemically treated crop residues

Abstract: Five studies were conducted to determine nutrient digestibility and performance of lambs and steers fed thermochemically treated crop residues and distillers dried grains with solubles (DDGS) as a corn replacement pellet (CRP; 75% residue:25% DDGS, DM basis). Fifteen Hampshire, Suffolk, or Dorset wethers (BW 33.3 +/- 5.0 kg) were utilized to evaluate nutrient digestibility of the unprocessed native (NAT) and CRP [Exp. 1: wheat straw (WS); Exp. 2: corn stover (CS); Exp. 3: switchgrass (SWG) and corn fiber:wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
8
2
Order By: Relevance
“…However, we did not observe any difference in DM or OM digestibility between the treated diets and CON. Differences between the results in the present study and those of Sewell et al (2008) could be related to the amount of corn replaced and the fact that both corn and roughage were replaced in this work.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…However, we did not observe any difference in DM or OM digestibility between the treated diets and CON. Differences between the results in the present study and those of Sewell et al (2008) could be related to the amount of corn replaced and the fact that both corn and roughage were replaced in this work.…”
Section: Discussioncontrasting
confidence: 82%
“…They concluded the addition of roughage in diets containing WDGS appears to have effects similar to those observed in grain-based diets. Sewell et al (2008) fed lambs treated (processed in a manner similar to that described above with 5% CaO, DM basis) pellets composed of wheat straw or corn stover at 30% of diet DM. They noted improvements in diet DM and NDF digestibilities of 9.7% and 48.3%, respectively, for treated wheat straw compared with the native form.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the DM digestibility was higher for the RWR treatment than the other treatments, and no difference was observed between the RCS, RCG, and CON treatments. Differences between the results in the present study and those of Sewell et al (2009) could be related to differences in animals used, diet composition, and the type and amount of feed replaced.…”
Section: Nutrient Digestibilitycontrasting
confidence: 60%
“…Effects of T-CS with by-product inclusion have also been studied previously. Sewell et al (2009) combined T-CS (processing similar to the method described above with 5% CaO, DM basis) with DDGS to create a CG replacement pellet for lambs. They found that the DM, NDF, and ADF digestibility were improved for T-CS compared with the native form.…”
Section: Nutrient Digestibilitymentioning
confidence: 99%
“…typically making up at least 50% of the diet (DM basis). Sewell et al (2008) fed Holstein steers (n = 32) a diet that replaced all of the DRC with pellets that contained 25% (DM basis) dried distillers grains plus solubles (DDGS) and CaO-treated (5% DM basis) wheat straw or corn bran (in varying proportions) that made up the majority of the pellet composition. In that study, no difference in ADG was observed but replacing all of the DRC increased DMI, which lead to 11.9% (corn fiber:wheat chaff blend) and 25.8% (wheat straw) reductions in G:F compared with a CON diet that contained 50% DRC, 25% DDGS, and 15% corn silage (DM basis).…”
mentioning
confidence: 99%